2015
DOI: 10.1016/j.ijhydene.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

New crystal structure of Nd2Ni7 formed on the basis of stacking of block layers

Abstract: Available online xxxKeywords: Hydrogen storage material Orderedisorder (OD) theory Polytype Scanning transmission electron microscopy Superlattice structure La 2 Ni 7 a b s t r a c tThe new crystal structure of the intermetallic compound (Nd,Mg) 2 (Ni,Al) 7 has been determined by scanning transmission electron microscopy and electron diffraction. This crystal structure is different from that (either 2H or 3R) usually reported for the intermetallic compound R 2 T 7 (R: rare-earth elements and T: transition-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our recent results on the crystal structure analysis for the 18 R -type LPSO phase in the Mg-Al-Gd system, however, revealed that the LPSO phase in the Mg-Al-Gd system should not be described as a ‘LPSO’ phase any longer in a strict sense in crystallography because of the existence of the in-plane ordering of Gd and Al atoms in the four consecutive atomic layers enriched with them in the 6-layer structural block 15 . Instead, the crystal structure of the ‘LPSO-type’ phases in the Mg-Al-Gd system is best described with the concept of the order-disorder (OD) structure 1523 , in which a crystal structure is described with the symmetry of an OD layer (corresponding to a 6-layer structural block) and the relative relation between adjacent two OD layers 15,17,18 . Then, there is a possibility that a series of LPSO-type phases with an OD structure (i.e., OD phases) is formed in Mg-Al-RE ternary systems, although the OD phases have recently been found to develop also in the Mg-Zn-Y system when the Zn/Y concentrations are high 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…Our recent results on the crystal structure analysis for the 18 R -type LPSO phase in the Mg-Al-Gd system, however, revealed that the LPSO phase in the Mg-Al-Gd system should not be described as a ‘LPSO’ phase any longer in a strict sense in crystallography because of the existence of the in-plane ordering of Gd and Al atoms in the four consecutive atomic layers enriched with them in the 6-layer structural block 15 . Instead, the crystal structure of the ‘LPSO-type’ phases in the Mg-Al-Gd system is best described with the concept of the order-disorder (OD) structure 1523 , in which a crystal structure is described with the symmetry of an OD layer (corresponding to a 6-layer structural block) and the relative relation between adjacent two OD layers 15,17,18 . Then, there is a possibility that a series of LPSO-type phases with an OD structure (i.e., OD phases) is formed in Mg-Al-RE ternary systems, although the OD phases have recently been found to develop also in the Mg-Zn-Y system when the Zn/Y concentrations are high 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…First, each structural block in the Mg-Al-Gd LPSO phases have a long-range in-plane order, which is characterized by a periodic arrangement of Al 6 Gd 8 atomic clusters with the L1 2 -type atomic arrangement in the Gd and Al-enriched four consecutive atomic planes. Second, although the Mg-Al-Gd LPSO phases have the perfectly ordered structure in each structural block, they generally exhibit one-dimensional disorder in the stacking of the structural blocks and consequently, their crystal structures are best described with the crystallographic concept of the order-disordered (OD) structure [13,15,[18][19][20][21][22][23]. The Mg-TM-RE LPSO phase with an OD structure is hereafter designated as the Mg-TM-RE LPSO/OD phase.…”
Section: Introductionmentioning
confidence: 99%
“…Long-period stacking order phases are further complicated by in-plane ordering in 14H and 18R types (Kishida et al, 2015;Kim et al, 2018b). This complication manifests itself with the presence of L1 2 type clusters, and the order is violated in one dimension, leading to the definition of order-disordered crystallographic structure in some Mg-TM-RE alloys (Yokobayashi et al, 2011a;Okamoto et al, 2014;Iwatake et al, 2015;Kishida et al, 2015Kishida et al, , 2017. The in-plane order may be a long-range type as in Mg-Al-Gd system Tane et al, 2015;Kim et al, 2018b) or may be composition dependent as in Mg-Y-Zn system, being present more locally in relatively dilute alloys, and long-range type in richer Mg-Y-Zn alloys (Egusa and Abe, 2012).…”
Section: Systems Containing Lpso Phasesmentioning
confidence: 99%